Relevance of dissolved organic nutrients for the Arctic Ocean nutrient budget - Sinhué Torres‐Valdés; Takamasa Tsubouchi; Emily Davey; Igor Yashayaev; Sheldon Bacon (Geophysical Research Letters)
Abstract We ask whether dissolved organic nitrogen (DON) and phosphorus (DOP) could account for previously identified Arctic Ocean (AO) inorganic nutrient budget imbalances. We assess transports to/from the AO by calculating indicative budgets. Marked DON:DOP ratio differences between the Amerasian and Eurasian AO reflect different physical and biogeochemical pathways. DON and DOP are exported to the North Atlantic via Davis Strait potentially being enhanced in transit from Bering Strait. Fram Strait transports are balanced. Barents Sea Opening transports may provide an additional nutrient source to the Barents Sea or may be locked within the wider AO Atlantic Water circulation. Gaps in our knowledge are identified and discussed.